Activation of the Immune Response of the Spleen by Using Low Level Laser (LLL) for Treatment of Mice Inoculated with Mammary Gland Carcinoma - Khaleel, Aida Z. (Iraqi Journal of Cancer and Medical Genetics, 2013)
Regional immune response with mammary gland carcinoma was studied statistically. However the prognostic value remains conflicting. This study was conducted on thirty normal mice which were inoculated with mammary gland carcinoma. The tumour size of the animals under study were measured before and after laser irradiation by using a vernier and compared with that of non irradiated animals with laser (control group). The aim of this study was to evaluate the effect of low level laser (LLL) on increasing the response of immune system by stimulating the spleen action to inhibit the cancer cell activity and then decrease the tumour size of inoculated mice. The results of the gross observation showed enlargement in the irradiated spleen in comparison with that of non irradiated ones. It could be said that the enlargement which occurred in the spleen proved that there was an increase in immune response by using laser stimulation. From this study, it may concluded that low level laser(LLL) was an efficient tool in stimulating the defense cells that found in the spleen which attack the cancer cells locally which resulted in decreasing the tumour size of the irradiated inoculated mice.